1997
DOI: 10.1016/s0169-5150(97)00023-6
|View full text |Cite
|
Sign up to set email alerts
|

Consumption risk, farm characteristics, and soil conservation adoption among low-income farmers in the Philippines

Abstract: This paper investigates patterns of soil conservation adoption among low‐income farmers in the Philippines. A model is presented that focuses attention on the role ot assets and consumption risk in conservation adoption decisions. Results Iron, a reduced‐form probit model of adoption are reported. These econometric findings indicate that patterns of soil conservation adoption reflect relative risk considerations in addititon farm and household characteristics. Farm size, tenure security, labor availability, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 22 publications
(18 reference statements)
4
30
1
1
Order By: Relevance
“…The available farm area is positively related to farmer's decision to adopt cropping systems that can help to mitigate climate change. This finding can be explained by the fact that multiple cropping systems such as crop associations and rotations require that farmers possess larger farm size, as a large farm size may facilitate longer rotations (Shively, 1997). This finding is in line with some earlier studies on innovation adoption that predicted higher adoption rate on large farms (Feder & O'Mara, 1981;Feder et al, 1985;Shively, 1997).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The available farm area is positively related to farmer's decision to adopt cropping systems that can help to mitigate climate change. This finding can be explained by the fact that multiple cropping systems such as crop associations and rotations require that farmers possess larger farm size, as a large farm size may facilitate longer rotations (Shively, 1997). This finding is in line with some earlier studies on innovation adoption that predicted higher adoption rate on large farms (Feder & O'Mara, 1981;Feder et al, 1985;Shively, 1997).…”
Section: Resultssupporting
confidence: 86%
“…This finding can be explained by the fact that multiple cropping systems such as crop associations and rotations require that farmers possess larger farm size, as a large farm size may facilitate longer rotations (Shively, 1997). This finding is in line with some earlier studies on innovation adoption that predicted higher adoption rate on large farms (Feder & O'Mara, 1981;Feder et al, 1985;Shively, 1997). For example the study by Scherr (1995) revealed higher adoption rates for agroforestry on large farms.…”
Section: Resultssupporting
confidence: 82%
“…The stock of soil available to a farmer is essentially an economic asset that can be exploited through cultivation to yield a stream of present and future income (Barbier 1990). Often, the return for practicing soil conservation can be long in coming, a feature that helps explain low adoption rates (Shively 1997). However, delays in payback do not completely explain low rates of investment, even if subjective discount rates are high.…”
mentioning
confidence: 99%
“…Las investigaciones que analizan la adopción de medidas de conservación de suelos a través de modelos probit y logit (Shively, 1997;Shiferaw y Holden 1998, Lucila et al 1999, o que abordan, a nivel descriptivo, la adopción de medidas de conservación del suelo con características históricas y culturales de los asentamientos agrícolas (Walters et al, 1999), o a través de técnicas multivariantes discriminantes (Earle et al 1979).…”
Section: Estado De La Cuestión En La Evaluación Económica De La Erosiunclassified